PERAN MEDIA SOSIAL DALAM MENINGKATKAN LITERASI HADIS DI MASA KINI - Najwa Ahimsa; Agus Suyadi Raharusun; Mila Melyani (Al-Mu'tabar, 2025)
his study examines the role of social media in improving hadith literacy today, especially in the midst of the rapid development of digital technology. Social media such as TikTok, YouTube, Instagram, and educational websites have become new means of conveying hadith in a way that is more interesting, easy to understand, and quick to reach a wide audience. The purpose of this study is to analyze how social media is used as an educational and da'wah tool in conveying hadith effectively. This research uses a qualitative approach with a desk study method, by collecting data from various relevant literature, journals, articles, and digital platforms. The results showed that social media contributes greatly to the interactive dissemination of hadith, although challenges such as the spread of false hadith still need to be watched out for. The use of takhrij and jarh wa ta'dil methods has become more accessible thanks to digital libraries such as Maktabah Syamilah and Dorar.net. In addition, the HOT-DAY app proves that hadith literacy can be instilled in children from an early age in a fun way. Thus, social media proves to be a strategic medium in strengthening the understanding and dissemination of hadith widely and contextually in the modern era.